Degradation of naphthalene with magnetic bio-char activate hydrogen peroxide: Synergism of bio-char and Fe–Mn binary oxides. (1st September 2019) - Li, Ling; Lai, Cui; Huang, Fanglong; Cheng, Min; Zeng, Guangming; Huang, Danlian; Li, Bisheng; Liu, Shiyu; Zhang, MingMing; Qin, Lei; Li, Minfang; He, Jiangfan; et al.
Abstract: This study investigated the hydrogen peroxide (H2 O2 ) activation potential of Fe–Mn binary oxides modified bio-char (FeMn/bio-char) for the degradation of naphthalene, the dominant PAHs in drinking water. Results showed that FeMn/bio-char exhibited 80.7- and 2.18-times decomposition rates towards H2 O2 than that of pure bio-char and Fe–Mn binary oxides, respectively, and consequently the FeMn/bio-char/H2 O2 photo-Fenton system presented highest naphthalene removal efficiency. The enhanced catalytic activity could be ascribed to the synergistic effect of the combination of bio-char and Fe–Mn binary oxides, such as promoting the adsorption capacity towards contaminant, increasing concentration of persistent free radicals (PFRs) and introducing Fe–Mn binary oxides as new activator. According to the batch-scale experiments, FeMn/bio-char/H2 O2 photo-Fenton system could degrade naphthalene effectively at a wide pH ranges, and 82.2% of naphthalene was degraded under natural pH of 5.6 within 148 min. Free radicals quenching studies and electron spin resonance (ESR) analyses verified that the dominant free radical within FeMn/bio-char/H2 O2 photo-Fenton system was hydroxyl radical (OH). According to the preliminary analysis, the generation of OH were ascribed to the activation of H2 O2 by Fe (II), Mn (II) and PFRs on the catalyst surface. The mainly degradation intermediates of naphthalene were identified by GC-MS analysis. Consequently, the possible degradation pathways were proposed. Moreover, naphthalene degradation experiments were also conducted in river, tap water, industrial wastewater as well as medical wastewater, and the results indicated that the FeMn/bio-char/H2 O2 photo-Fenton system was effective in the treatment of naphthalene in natural waters. This study brings a valuable insight for the potential environmental applications of modified bio-char. Graphical abstract: Image 1 Highlights: Fe–Mn binary oxides modified bio-char was studied as a novel H2 O2 activator. FeMn/bio-char/H2 O2 can work effectively at neutral initial pH. Controlling factors of naphthalene degradation were evaluated. .OH was mainly responsible for the degradation of naphthalene. The possible mechanism of H2 O2 activation was elucidated.